Web Based Production Scheduling Information System for a Shrimp Paste Factory Utilizing the Waterfall Method - Hasibuan, Agung Setiawan; Suendri, Suendri; Sibarani, Fathiya Hasyifah (Information Technology and Science (ITScience), 2024)
Communication was essential in various aspects of life due to the rapid development of information technology, including in the management of educational institutions and companies. PT. Sumber Nelayan Indonesia faced issues in production scheduling, where the process was still done manually using bookkeeping. This caused delays in order fulfillment, primarily due to machine breakdowns and human resource challenges that impacted the production process. Additionally, the company struggled to manage order data and machine capacity, making it difficult to estimate order completion times and the amount of output produced. This research aimed to develop a web-based management information system for scheduling using the Laravel framework to assist PT. Sumber Nelayan Indonesia in managing scheduling more effectively and efficiently. The research method employed was R&D, with the system development model following the waterfall method, utilizing PHP as the programming language and MySQL as the database. System testing was conducted using black box testing. The results of the research indicated that the developed system could help the company schedule production more efficiently, reduce delays, and improve operational efficiency.